Sunbelt rising : the politics of place, space, and region - Dochuk, Darren; Nickerson, Michelle M. (Politics and culture in modern America., 2011)
This volume examines patterns of growth, government organization, and cultural representation that created a new region across the nation's southern rim following World War II. Essays explain how ideology and political economy restructured space within the Sunbelt, making the landscape and lives of its inhabitants more uniformly metropolitan.